Young Speakers: A Pilot Study of Gaelic Bilinguals’ Language Practices - Macleod, Michelle; Macleod, Marsaili (Studia Celtica Posnaniensia, 2018)
Studies of primary school pupils’ Gaelic to date have largely relied on criterion referenced tests to measure attainment against curricular expectations: with only NicLeòid’s (2015) work on student attitudes and Nance’s research (e.g. 2013 and 2015) on comparative phonology bucking this trend. There is a surprising lack of information or research about the language forms and bilingual repertoire of young speakers. A better understanding of young people’s language practices requires the Gaelic research community to develop datasets from spontaneous interactions. This paper draws on a pilot study with a primary 5-6 school cohort in Gaelic-medium education. Using a combination of audio and audio-visual data from the classroom together with data on young speakers’ language attitudes, this paper examines pupils’ determination and strategies to maintain the classroom language as Gaelic. The results of this pilot study can inform the development of new methodologies for collaborative research with the school community on children’s linguistic development and attainment. Such research, it is argued, is necessary in light of the dependency of the Gaelic language planning model on the primary school for the production of new Gaelic speakers.